THE ECONOMIC EFFECTS OF ASSOCIATION PROCESS TO THE EUROPEAN UNION ON EXPORT PERSPECTIVES OF SERBIAN AGRICULTURE - Petrović, Pero; Antevski, Miroslav; Milanović, Milan R. (Economics of Agriculture, 2006)
The process of Serbian integration to the World trading system and the European Union has a huge influence to current and future changes in economic structure. Effects of that process should become stronger as Serbia bring closer to membership of European Union. The agriculture (including all sectors without industry) and linked sectors will sustain very strongly the effects of association process because of high protection level of agriculture in the European Union and in many other countries. With Serbian accession to the European Union, its agriculture will share appropriate protection with other member states, lower than actual one, but it will be a subject of more stronger competition in the internal market of the European Union. The accession period of time should and can be used for achieving an european productivity level in agriculture, which is lower than in USA and other countries, building of optimal structure in agricultural production and cattlebreeding, organic food production, integral development of rural areas, and for strong link up together all related sectors. A joint ventures in agriculture should be the way to export expansion to third markets.